Division of Labor Between Two Actin Nucleators—the Formin FH1 and the ARP2/3 Complex—in Arabidopsis Epidermal Cell Morphogenesis - Cifrová, Petra; Oulehlová, Denisa; Kollárová, Eva; Martinek, Jan; Rosero, Amparo; Žárský, Viktor; Schwarzerová, Kateřina; Cvrčková, Fatima (Frontiers in Plant Science, 2020)
The ARP2/3 complex and formins are the only known plant actin nucleators. Besides their actin-related functions, both systems also modulate microtubule organization and dynamics. Loss of the main housekeeping Arabidopsis thaliana Class I membrane-targeted formin FH1 (At3g25500) is known to increase cotyledon pavement cell lobing, while mutations affecting ARP2/3 subunits exhibit an opposite effect. Here we examine the role of FH1 and the ARP2/3 complex subunit ARPC5 (At4g01710) in epidermal cell morphogenesis with focus on pavement cells and trichomes using a model system of single fh1 and arpc5, as well as double fh1 arpc5 mutants. While cotyledon pavement cell shape in double mutants mostly resembled single arpc5 mutants, analysis of true leaf epidermal morphology, as well as actin and microtubule organization and dynamics, revealed a more complex relationship between the two systems and similar, rather than antagonistic, effects on some parameters. Both fh1 and arpc5 mutations increased actin network density and increased cell shape complexity in pavement cells and trichomes of first true leaves, in contrast to cotyledons. Thus, while the two actin nucleation systems have complementary roles in some aspects of cell morphogenesis in cotyledon pavement cells, they may act in parallel in other cell types and developmental stages.